Männlichkeiten Geschlechterkonstruktionen in pädagogischen Institutionen - Budde, Jürgen; Thon, Christine; Walgenbach, Katharina (Jahrbuch Frauen- und Geschlechterforschung in der Erziehungswissenschaft, 2014)
Masculinities are the focus of current debates in education policy and educational science. If one considers the discussion about 'boys as 'losers of education', masculinity as such already seems to be a risk of discrimination. At present, there are efforts to focus particularly on men or masculinities in educational institutions: Initiatives for more male specialists in day-care centres or schools want to create more educational justice through the mere presence of men. In doing so, masculinity is currently identified as a professional resource. An ascribed male gender already seems sufficient in itself for the quality of pedagogical professionalism. Constructions of masculinities also influence the establishment of institutional structures.